Research on the reform and effect evaluation of three-dimensional motion animation blended teaching based on fuzzy evaluation model - Intan Khasumarlina Mohd Khalid (Tanjung Malim, 2024)
Research on the reform and effect evaluation of three-dimensional motion animation blended teaching based on fuzzy evaluation model by Intan Khasumarlina Mohd Khalid